Flexible Approach Path (FAP) for Effective Learning Process in Self Exploration Education System (SEES) - Muhammad Fazil, Ahmad (2018)
The purpose of this study is to develop a Flexible Approach Path (FAP) for effective Self Exploration Education System (SEES) practice for adult learning. In practice, SEES still acutely focuses on transmitting facts instead of encouraging personal exploration. A major barrier to the uptake and integration of new technologies in teaching and learning is the lack of personal experience of online learning on the part of those involved in learning and in the preparation of materials and methods to support the learning. This project addresses by introducing a FAP to support one’s own learning, within a semi-formal community structure using 45 = 40 end-users. This project focuses on the FAP that includes six dimensions (Invention, Recommendation, Explanation, Demonstration, Understanding, and Recall) which can impact: time; the content of the course; entry requirements; instructional approaches and resources; delivery and logistics - each with several aspects. It is applicable to all learning-development situations without being merely restricted to self-instruction or Distance Learning. For the persons who are not familiar with the Flexible Approach, e.g., those who are familiar with face-toface/ fieldwork approach, they may wonder why and when the Flexible Approach is applicable. The Flexible Approach is applicable in a case where a learner who can conduct learning on his/her over for certain subjects, thus decreasing the demand for an instructor. A missed learning session does not have to be replaced because the material is already there. They help a trainee who takes a little longer than the other learners to comprehend certain concepts/materials. In addition, it is suitable to be applied in situations when the time is a constraint to limit face to face interaction. In all the above scenarios, the Flexible Approach to learning and development can be used as a very realistic alternative.